Corporate tribe. - Braun, Danielle, author.
1 online resource.
Keywords: No challenge is entirely new. In 60,000 years of human existence, nearly every problem we face in modern business has already been seenand solved. We just have to figure out how to apply that age-old tribal wisdom to our current circumstances. The Corporate Tribe will take you on a journey to discover the essence of culture and the secret to successful change programs. Along the way, it will introduce you to the cultural traditions of different people across the globe and provide you with the practical tools you need to apply what you find to today's organizations. Through thirty compelling stories, The Corporate Tribe will reveal what, deep down, you already know. At turns unfamiliar and disruptive, illuminating and inspirational, The Corporate Tribe offers a powerful paradigm and skillset for tackling organizational and leadership challenges in the twenty-first century and beyond. It is a book for leaders, consultants and advisors who are looking for a fresh perspective and proven solutions, for those who want to build strong communities that are safe for diversity and ready for change. Danielle Braun and Jitske Kramer are corporate anthropologists. They look at organizations as tribes, organizational charts as kinship systems, leaders as chiefs and mission documents as totem poles. Travel with them to places where spirits linger after death, magic is real and rituals are the key to maintaining order and facilitating transition. You will never look at your organization--or approach its problems--the same way again.